A case report on caesarean myomectomy - Mishra, Shalini; Sinha, Namrata; Prasad, Anima; Kumar, Amrish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Routine myomectomy at the time of caesarean section has been condemned in the past due to fear of uncontrolled haemorrhage and peripartum hysterectomy. It is still a topic of debate worldwide. However, in recent years, many case studies of caesarean myomectomy have been published validating its safety without any significant complications like excessive blood loss. We describe the case of a 23-year-old nulliparous women at 38 weeks of pregnancy with history of previous abortion. Her ultrasound was suggestive of singleton live intrauterine pregnancy with multiple intramurals and subserosal uterine fibroids seen in fundus, body region, posterior and anterior myometrium with largest fibroid of size 9×6.1 cm. The patient was taken up for elective caesarean section along with caesarean myomectomy. Live baby was delivered and successful myomectomy was done. Prophylactically oxytocin drip was given and intra myometrial carboprost was given to avoid blood loss. Patient was discharged on post-operative day 12 without any complications. Routine myomectomy at the time of caesarean section is not a standard procedure. However, it may be considered a safe option in carefully selected cases in the hands of an experienced obstetrician.